A comparative study on the phenolic bioaccessibility, antioxidant and inhibitory effects on carbohydrate-digesting enzymes of maca and mashua powders - Paucar-Menacho L.M. (2020)
The polyphenolic content of dehydrated maca (MA) and mashua (M) powders, promising functional ingredients, and their antioxidant activity and inhibition of carbohydrate digestion was evaluated following in vitro gastrointestinal digestion (GID). Moreover, the impact of steaming on bioaccessibility and bioactivity of the M phenolic fraction was investigated. MA phenolic fraction composed mainly of caffeic-4-O-glucosides showed high bioaccessibility (117.8%), antioxidant activity (142.9 μmol Trolox equivalents, TE/g) and weak effectiveness to inhibit carbohydrate digestion after GID. Anthocyanins were the major compounds in the M phenolic fraction with low bioaccessibility (22.4%), although a superior antioxidant activity (446.7 μmol TE/g) and modest inhibitory effects on carbohydrate digestion after GID. Generally, bioaccessibility and bioactivity of M decreased after steaming process. MA and M powders contain appreciable concentrations of phenolics, although M polyphenols were more effective on modulating carbohydrate digestion. © 2020 Elsevier Ltd